(untitled) (Research, Society and Development, 2021)
The aim of this study was to report a clinical case of osteonecrosis caused by bisphosphonates and its treatment with the aid of laser therapy. Low-level laser therapy (LLLT) is a resource used that is characterized by photobiostimulation and photobiomodulation, promoting analgesia and anti-inflammatory effects and can also be a tool for treating osteonecrosis induced by bisphosphonates (BFs), when associated also to drug therapy. The present case is a 63-year-old patient, leukoderma, with thyroid disorder and osteoporosis, making continuous use of medicaments classified as BF’s. He had a dental fracture and sensitivity to cold and treatment started with prophylaxis. After radiography of the dental elements, restorations were performed and tooth extraction (element 46). In the postoperative period, the patient reports pain and a bone exposure were observed clinically in the region of the extracted area, with osteonecrosis being diagnosed. Drug therapy was promptly applied and the use of LLLT was chosen as an adjunctive and supportive therapy. It is plausible to infer the need for attention to patients undergoing drug treatment with bisphosphonates, fully evaluating the best treatment for the possible occurrence of osteonecrosis in view of LLT as an effective complementary therapeutic approach.